Molecular attributes and apoptosis-inducing activities of a putative serine protease isolated from Tiger Milk mushroom (Lignosus rhinocerus) sclerotium against breast cancer cells in vitro - Hui Yeng Y. Yap; Nget Hong Tan; Szu Ting Ng; Chon Seng Tan; Shin Yee Fung (PeerJ, 2018)
Background The highly valued medicinal tiger milk mushroom (also known as Lignosus rhinocerus) has the ability to cure numerous ailments. Its anticancer activities are well explored, and recently a partially purified cytotoxic protein fraction termed F5 from the mushroom’s sclerotial cold water extract consisting mainly of fungal serine proteases was found to exhibit potent selective cytotoxicity against a human breast adenocarcinoma cell line (MCF7) with IC50 value of 3.00 μg/ml. However, characterization of its cell death-inducing activity has yet to be established. Methods The mechanism involved in the cytotoxic activities of F5 against MCF7 cells was elucidated by flow cytometry-based apoptosis detection, caspases activity measurement, and expression profiling of apoptosis markers by western blotting. Molecular attributes of F5 were further mined from L. rhinocerus’s published genome and transcriptome for future exploration. Results and Discussion Apoptosis induction in MCF7 cells by F5 may involve a cross-talk between the extrinsic and intrinsic apoptotic pathways with upregulation of caspase-8 and -9 activities and a marked decrease of Bcl-2. On the other hand, the levels of pro-apoptotic Bax, BID, and cleaved BID were increased accompanied by observable actin cleavage. At gene level, F5 composed of three predicted non-synonymous single nucleotide polymorphisms (T > C) and an alternative 5′ splice site. Conclusions Findings from this study provide an advanced framework for further investigations on cancer therapeutics development from L. rhinocerus.